3D limit analysis of masonry pavilion domes on octagonal drum subjected to vertical loads - Carlalberto Anselmi; Filomena Galizia; Eduardo Saetta (Fracture and Structural Integrity)
Within the framework of limit design applied to masonry structures, this paper aims at analyzing the different behavior of a pavilion dome according to the adopted construction and reinforcement technologies. By using the static theorem applied to the dome discretized in rigid macro-blocks of variable shape aligned along parallels and meridians, a mathematical model have been constructed in order to search for the load collapse multiplier, and thus to evaluate the degree of structural safety. Then, the associated failure mechanism is represented at the instant in which the collapse is reached. The program that implement the modeling is sufficiently versatile and, in addition to the mechanical characteristics, allows to define the intrados profile, the thickness variability, as well as to insert any window opening in the drum, the lantern at the top and the hoops at each level. The results shown here concern some numerical applications carried out on a theoretical dome, as well as those related to a first approach to the analysis of the dome of Santa Maria del Fiore in Florence by Brunelleschi.